الوظيفة الإعلامية في نظرية ياكبسون: تقاطعات اللغة الأدبية والخطاب الصحفي في ضوء الدارة التواصليّة - عواركه هيثم قاسم (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study investigates the media function in light of Roman Jakobson’s linguistic theory, applying a stylistic-comparative method to journalistic texts from Lebanese, Arab, and global sources. It demonstrates how communicative functions intersect in shaping the media message within a dynamic transmission model.